Death Due to Traumatic Amniotic Fluid Embolism Following a Fall From a Bed: A Case Report - Sushma Chandulee Kancharla; Mopuri Venkateswarlu; Lakshmi Kalavathi C; Sai Prasad B V; Nishanth V S; Kattamreddy Ananth Rupesh (National Board of Examinations Journal of Medical Sciences, 2024)
Amniotic Fluid Embolism (AFE) is a rare obstetric emergency with a potentially fatal outcome, occurring in approximately 1.9 to 6.1 cases per 100,000 deliveries, with variations observed among different countries. Obstetric management continues to be the most common preceding event associated with AFE, making it the primary contributing factor. However, traumatic AFE cases are being typically reported as isolated case reports in literature. While previous case reports on the traumatic basis of AFE have primarily associated AFE with blunt-force abdominal trauma resulting from car accidents and evident gross injuries, this article presents a unique case of AFE following minor blunt trauma from a self-fall from a height of 2.5 ft, where no macroscopic lesions were observed. The autopsy lung histopathology exhibited alveolar spaces filled with serous fluid and lymphocytes, as well as emboli composed of fatty material in blood vessels. Some blood vessels contained keratinous emboli. Severe pulmonary oedema and embolized vessels were consistently observed throughout the lung sections. We hypothesise that a simple fall from a height of 2.5 feet onto a firm surface, leading to transmitted blunt force to the abdomen, may trigger AFE by disrupting the flow dynamics of the foeto-placento-maternal circulation. Despite the absence of gross injuries, the underlying pressure transmission is emphasized as a significant factor in AFE initiation due to the disruption of the microvasculature. This case report highlights the importance of recognizing the possibility of AFE even in cases of seemingly minor trauma without visible external signs.